Real-world assessment of listener preference for hearing aid technology levels in socially involved situations - Glista, Danielle; O'Hagan, Robin; Beh, Krystal; Crukley, Jeffery; Scollie, Susan; Cornelisse, Leonard (Frontiers in Audiology and Otology, 2024)
IntroductionCurrent hearing aids have an abundance of feature options and technologies. It is important to understand the clinical impact of hearing aid technology selection and how to individualize fittings to optimize hearing aid performance according to listening environment. To probe the naturalistic listening experiences researchers can use in-situ outcome measures. Survey-based real-world assessments can increase knowledge of hearing aid users' everyday scenarios, beyond the limits of lab-based scenarios. This study aimed to assess the relationship between subjective preference ratings of adult listeners and hearing aid technology level using Ecological Momentary Assessment (EMA). A secondary research question explored survey completion as a function of real-world participation in socially involved situations.MethodsThis study aimed to capture and assess in-the-moment listening situations and participant preference for hearing aid technology levels, using EMA through an app-based survey. Surveying was completed indoors (at home), indoors (away from home); and outdoors, and while in a listening situation with at least one communication partner. Fourteen older adults, aged 61–82 years, who were experienced bilateral hearing aids users were included in this study. Participants completed a 2-week acclimatization period wearing study-provided hearing aids, and a 2-week data collection period. In-situ surveying was used to evaluate technology-level preference in real-world listening situations with at least one communication partner. Survey data captured in-the-moment details surrounding environment, activity, and listening preference. Mixed methods were used to analyze the data, including Bayesian analyses for preference data and content analysis for text-based survey responses, including the use of the International Classification of Functioning, Disability and Health to guide activity categorization.ResultsAcross a wide variety of categorized activities, participants demonstrated a preference for mid- to high-level hearing aid technologies when compared to the lowest level. Technology preference also varied according to reported activity location.DiscussionThe use of in-situ surveying provided a broader understanding of hearing aid users' listening environments when conversing with one or more communication partners and related technology preferences. EMA was found to be a feasible method of data collection for this cohort and may help guide clinical, person-centered selection of technology level.